1996
DOI: 10.1074/jbc.271.17.10405
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Human Erythropoietin Gene Expression by the TR2 Orphan Receptor, a Member of the Steroid Receptor Superfamily

Abstract: A DNA response element, TR2RE-EPO (5-TCTGAC-CTCTCGACCTAC-3) has been identified in the 3-minimal hypoxia-inducible enhancer of the human erythropoietin gene for the TR2 orphan receptor, an androgenrepressed transcription factor and a member of the steroid/thyroid hormone receptor superfamily. Electrophoretic mobility shift assay showed a specific binding with high affinity (K d ‫؍‬ 0.14 nM) between the TR2 orphan receptor and the TR2RE-EPO. Our data further indicated that this specific binding is not due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…54 Other than that, some previous reports suggest that the effect of E 2 on Epo gene regulation acts through steroid hormone receptors; there are tandem repeats of steroid hormone receptor response element half-sites in the Epo promoter and enhancer regions, 55 and the testicular receptor 2 (TR2) orphan receptor, which shares structural homology with members of the steroid/ thyroid hormone receptor superfamily, suppresses Epo gene expression. 56 Another recent report demonstrated that E 2 attenuated Epo expression by interfering with hypoxic increases in HIF-1␣ protein through an estrogen receptor-dependent mechanism. 57 However, the results indicating possible involvement of steroid hormone receptors or HIF-1␣ were all obtained from in vitro experiments, and we actually observed that E 2 did not inhibit Epo induction in vitro using Epo-producing Hep3B cells derived from human hepatoma cells (data not shown).…”
Section: Iron and Estradiol Effects On Epo 71mentioning
confidence: 99%
“…54 Other than that, some previous reports suggest that the effect of E 2 on Epo gene regulation acts through steroid hormone receptors; there are tandem repeats of steroid hormone receptor response element half-sites in the Epo promoter and enhancer regions, 55 and the testicular receptor 2 (TR2) orphan receptor, which shares structural homology with members of the steroid/ thyroid hormone receptor superfamily, suppresses Epo gene expression. 56 Another recent report demonstrated that E 2 attenuated Epo expression by interfering with hypoxic increases in HIF-1␣ protein through an estrogen receptor-dependent mechanism. 57 However, the results indicating possible involvement of steroid hormone receptors or HIF-1␣ were all obtained from in vitro experiments, and we actually observed that E 2 did not inhibit Epo induction in vitro using Epo-producing Hep3B cells derived from human hepatoma cells (data not shown).…”
Section: Iron and Estradiol Effects On Epo 71mentioning
confidence: 99%
“…Deletion in a PV is coherent with the known function of NFIA in erythropoiesis. [7][8][9] The calculated number of NFIA gene copy suggests that the deletion was present at the heterozygous state in almost all cells or homozygous in around half the cells. The moderate JAK2 V617F allele burden suggests that the mutation may have occurred on the background of the 1p31.3 deletion.…”
mentioning
confidence: 99%
“…5,6 NFIA regulates erythropoiesis through a network involving NR2C1, GATA1 and erythropoietin. [7][8][9] To determine whether NFIA could have a function in early leukemogenesis, we searched for alterations of the NFIA gene in 89 chronic hematopoietic diseases by using array-comparative genomic hybridization (aCGH) and DNA sequencing. Our series comprised 35 chronic myelomonocytic leukemias and 54 myeloproliferative disorders including 8 cases of polycythemia vera (PV), 42 cases of essential thrombocythemia and 4 cases of idiopathic myelofibrosis.…”
mentioning
confidence: 99%
“…It is also known that this gene encodes two isoform receptors, one retaining the entire ligand binding domain (LBD) and the other truncated at the LBD, which exhibit differential expression patterns in developing testes (24). The biological function of the full-length TR2 has been examined in a variety of systems, such as the cellular RA binding protein I promoter containing a direct repeat 4 (DR4) element (6), a RAR-responsive element (RARE) of the DR5 type from RAR␤ (24, 30), a DR2 from the simian virus 40 (SV40) promoter (26), and a DR2 from the erythropoietin gene promoter (27). In all tested systems, the full-length TR2 consistently represses reporter gene expression in cell cultures supplemented with either regular serum or charcoal-depleted serum.…”
mentioning
confidence: 99%